2017
DOI: 10.2147/dddt.s131503
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on endovascular treatment of (sub)acute critical limb ischemia: mechanical thrombectomy vs thrombolysis

Abstract: ObjectiveThe aim of this study was to compare different interventional methods for treatment of (sub)acute limb ischemia upon thrombotic occlusions of the lower extremity in terms of their safety and efficacy in a tertiary hospital setting.DesignThis is a retrospective, single-center study of non-randomized data.MethodsA total of 202 patients, including 26 critically ill patients, underwent rotational thrombectomy (Rotarex®), local thrombolysis (recombinant tissue plasminogen activator), or combination of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…149e151 A comparative (nonrandomised) study of Rotarex vs. thrombolysis showed similar technical results but better primary and secondary patency rates with fewer complications and shorter hospital stay in the Rotarex group. 152 This device can also aspirate more organised clot but cannot be used in smaller arteries below the knee. 153 Vessel perforation has been described as a device related complication.…”
Section: Iiamentioning
confidence: 99%
“…149e151 A comparative (nonrandomised) study of Rotarex vs. thrombolysis showed similar technical results but better primary and secondary patency rates with fewer complications and shorter hospital stay in the Rotarex group. 152 This device can also aspirate more organised clot but cannot be used in smaller arteries below the knee. 153 Vessel perforation has been described as a device related complication.…”
Section: Iiamentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of this system in the treatment of patients with ALI[ 14 - 18 ]. In this regard, a high success rate of > 98% was reported in a recent study, which elegantly demonstrated that purely mechanical thrombectomy by the Rotarex ® S system was safer and more effective than thrombolysis, which was associated with higher rates of major bleedings, longer hospitalization durations and higher costs[ 19 ]. Potential complications associated with the Rotarex ® S endovascular system is peripheral embolization of thrombotic debris in peripheral foot arteries (in most of the cases after additional balloon angioplasty and not directly related to Rotarex ® S thrombectomy) and vessel dissection or perforation in smaller vessels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized as an efficient and safe method to treat acute, subacute or even chronic occlusions or stenosis of peripheral vessels. [9][10][11][12][13][14] In addition, the company of Rotarex system also has another device -Aspirex which is created for thrombus aspiration for venous system such as deep venous thrombosis. [15] Due to venous valve issue, generally Rotarex system can not be used in venous system for thrombus aspiration.…”
Section: Discussionmentioning
confidence: 99%